2012
DOI: 10.1890/11-1792.1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the spatial scale of land use that most strongly influences overall river ecosystem health score

Abstract: Catchment and riparian degradation has resulted in declining ecosystem health of streams worldwide. With restoration a priority in many regions, there is an increasing interest in the scale at which land use influences stream ecosystem health. Our goal was to use a substantial data set collected as part of a monitoring program (the Southeast Queensland, Australia, Ecological Health Monitoring Program data set, collected at 116 sites over six years) to identify the spatial scale of land use, or the combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 53 publications
(97 reference statements)
1
59
0
4
Order By: Relevance
“…Variation due to land use changes (e.g., loss of riparian forest cover) was therefore explicitly accounted for beyond that due to natural variation. The study found that 60%-80% upstream riparian cover of mid-dense forest would be required to maintain acceptable river health outcomes for the region (see also Section 4), including diverse communities of macroinvertebrate and native fish species [19]. Overall forest cover in the catchments was also found to have a significant effect on river health, as measured by the water quality and nutrient indicators.…”
Section: Water Quality and The Ecology Of Riversmentioning
confidence: 94%
See 3 more Smart Citations
“…Variation due to land use changes (e.g., loss of riparian forest cover) was therefore explicitly accounted for beyond that due to natural variation. The study found that 60%-80% upstream riparian cover of mid-dense forest would be required to maintain acceptable river health outcomes for the region (see also Section 4), including diverse communities of macroinvertebrate and native fish species [19]. Overall forest cover in the catchments was also found to have a significant effect on river health, as measured by the water quality and nutrient indicators.…”
Section: Water Quality and The Ecology Of Riversmentioning
confidence: 94%
“…Contrary to common belief, much of the phosphorus running off the catchment is in the dissolved inorganic form or loosely bound to soils owing to release from soil during wetting events [28][29][30]. As a result, the phosphorus can directly stimulate phytoplankton blooms, although the spatial and temporal scales over which this occurs depends on the turbidity of inflowing waters (which alters light availability) and the size, timing and source of those waters [19].…”
Section: Water Quality and The Ecology Of Reservoirsmentioning
confidence: 95%
See 2 more Smart Citations
“…Conditions of topography and land use are also important factors that influence the water quality in lotic environments (Sheldon et al, 2012), requiring the use of methods of study that focus both the ecological and anthropogenic processes occurring in the landscape scale and/or in the watershed as a whole (Likens, 1984;Wiens, 1989;Zalewski, 2000;Turner et al, 2001;Tundisi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%